VTE primary prevention, including hospitalised medical and orthopaedic surgical patients - Granziera, Serena; Cohen, Alexander T. (Thrombosis and Haemostasis, 2015)
Primary prevention is the key to managing a significant proportion of the burden of venous thromboembolism (VTE), defined as deep venous thrombosis (DVT) or pulmonary embolism (PE). This is because VTE may lead to sudden death or are often misdiagnosed and therefore treatment is not feasible. Primary prevention usually commences in hospital as VTE following hospitalisation adds to the significant disease burden worldwide. Numerous medical, surgical and other risk factors have been recognised and studied as indications for prophylaxis. The risk of VTE continues following admission to hospital with a medical or surgical condition, usually long after discharge and therefore prolonged primary prophylaxis is often recommended. Clinical and observational studies in surgical patients show this risk extends for months and perhaps more than one year, for medical patients the risk extends for at least several weeks. For the specific groups of patients at higher risk of developing VTE primary prevention, either pharmaceutical or mechanical, is recommended. The aim of this review is to describe the population at risk, the main related risk factors and the approach to thromboprophylaxis in different populations.
Keywords: Venous thrombosis; prophylaxis; clinical studies; clinical trials; heparins/LMWH; oral anticoagulants